Shifts in the Traditional Culture. Folksongs in the 21st Century City - Nakienė, Austė (Tautosakos darbai, 2015)
The traditional culture existing in the city experienced considerable changes in the course of the last century. Rather than comprising continuous, gradual development, this change involved several radical cultural shifts, taking place in the 20th century (e. g. in the beginning of the century, in the 1960s, and 1990s). The article compares the urban, social and cultural changes in order to determine periods when the traditional culture experienced the most crucial transformations and when various new phenomena appeared. A clear shift in the urban culture took place in the 1960s in Lithuania, when a political “warming” of sorts could be felt and the pressure of the communist ideology was somewhat lighter. The economic growth was followed by the formation of the consumer society (although a rather different one from that emerging in the liberal countries), taking place in Vilnius, Kaunas, and other cities. The 1960s and the subsequent decades were characterized by a considerable variety of the urban culture in Lithuania, especially in its capital city. In the musical sphere, the state-supported academic music, the professionally performed folk music, and the show music were particularly thriving; but performances of jazz, rock and authentic folklore also gained momentum.The Lithuanian Folklore Theater, which started its activity in 1968 in Vilnius, can be presented as a typical example of the altered tradition. Director of this theater Povilas Mataitis and his wife, scenographer Dalia Mataitienė managed to achieve a subtle harmony between the folk tradition and their individual artistic expression, uniting in their performances elements of folklore and the modern art, and using small artistic forms, so typical to the folk art, to create complicate ambivalent compositions. Nevertheless, the stylistic shifts of the 1960s were best reflected in the rock music. The swinging two-part rhythm and open expressions of the individual feelings embodied a radical stylistic change at that time (although such means of expression are completely common and trivial today). Starting from the 1960s these innovations affected not only the urban composers, but also the folksong creators at the countryside.The significant cultural shift took place also after the Lithuanian independence was regained in 1990. The Soviet past was rejected, the Western notion of culture was willingly adopted, and the patterns of cultural life and financing were increasingly altered. The formerly state-supported cultural institutions and performers had to adapt to the free-market. At first, the cultural shift of the 1990s resembled an avalanche: the former unified whole – the coherent image of the national culture created during the Soviet times was shattered. Composers and authors plagued by various difficulties found respite, though, in the new kinds of the available information, the opened possibilities of getting to know the global culture, which had been hitherto almost impossible to gain access to. The epoch of postmodernity, characterized by free associations between various historical and cultural signs, was favorable to the continuation of traditions; therefore various transformations of folklore quickly appeared, musical styles from different periods and nations were abundant, and all sorts of their hybrids were created. A new thing establishing itself on the Vilnius pavement was hip hop – the Afro-American music and life style, born in the suburbs of New York. It was increasingly adopted and furthered by the Vilnius inhabitants, born in the concrete districts of the city, whose youth coincided with the years of the post-Soviet economic “shock-therapy”.The traditional music found its place in the city as well, growing as a moss on a stone. It is now performed both in the great ceremonious halls and in the small, stuffy premises, or simply outside during spring and summer. The city of the 21st century is characterized by such cultural phenomena as urban folklore, bard songs, live music, street music, post-folklore, indigenous culture, Baltic music, pagan art, improvisational music, underground music, etc. Urban tradition is a multifaceted and a multileveled one, its continuation constantly involves connecting different musical styles and respective communities.In the urban environment, the preservation of the folk music is no longer the concern of exclusively the representatives of the folklore movement; authors of different kinds are also involved, including the jazz and rock musicians, visual artists, IT specialists, and actors. Nowadays, the third generation is gradually involved into the urban folklore movement, as its pioneers, having already become grandparents, bring their grandchildren into the same halls and yards of the Old Town, where they used to perform in their youth. At the same time, new cultural wave created by the contemporary young people rises from the underground clubs, multimedia or electronic music labs, and artistic workshops. The young keep always creating something new, but this should not be regarded as a threat to the preservation of the urban folk tradition.
Keywords: -